Organizational Citizenship Behavior and Energy Transition in Energy-Intensive Industries: A Bibliometric Review - Bao, Chau Hoai; Linh, Nguyen Thi My; Hien, Tran Thi Ngoc (International Journal of Energy Economics and Policy, 2026)
This study aims to analyse the existing literature and identify major research trends at the intersection of organizational citizenship behavior and energy transition in energy-intensive industries. Data were retrieved from the Scopus database and include 155 English-language publications published between 2015 and 2025. A bibliometric analysis was conducted using R Studio (Bibliometrix/Biblioshiny) and VOSviewer to examine publication performance, influential journals and authors, geographical distribution, and thematic structures within the research domain. The results show a rapid expansion of research linking organizational behavior with energy transition, reflecting increasing scholarly attention to the behavioral and organizational dimensions of energy efficiency and low-carbon transition. The literature is mainly published in high-quality journals in energy economics, sustainability, environmental management, and organizational studies. Geographically, research activity is concentrated in Asia and Europe, with China emerging as the most productive contributor, followed by several European countries and other emerging economies. Keyword co-occurrence and thematic mapping identify four major research themes: organizational green management and sustainability foundations; pro-environmental and organizational citizenship behaviors and governance mechanisms; energy efficiency, energy consumption, and low-carbon transition dynamics; and system-level energy transition, policy, and stakeholder governance. The study also outlines future research directions to strengthen the integration of organizational citizenship behavior, energy economics, and sustainability perspectives in energy-intensive industries.